Rhipicephalus sanguineus sensu lato from dogs and dromedary camels in Riyadh, Saudi Arabia: low prevalence of vector-borne pathogens in dogs detected using multiplexed tandem PCR panel - Chandra, Shona; Smith, Karen; Alanazi, Abdullah D; Alyousif, Mohamed S; Emery, David; Šlapeta, Jan R (Folia parasitologica, 2019)
Despite the global distribution of the brown dog tick, Rhipicephalus sanguineus (Latreille, 1806) sensu lato (s.l.), limited information exists about their identity from the Arabian Peninsula. Ticks from free roaming urban dogs and dromedary camels in Riyadh, Saudi Arabia were morphologically identified, confirmed with scanning electron microscopy and characterised at mitochondrial DNA (cox1, 12S rDNA and 16S rDNA). A total of 186 ticks were collected from 65 free roaming dogs (n = 73) and 84 dromedary camels (n = 113). Morphologically, 5.9% (11/186) were R. sanguineus s.l. and Hyalomma spp. (93.5%, 174/186). From within R. sanguineus s.l., the presence of Rhipicephalus cf. camicasi Morel, Mouchet et Rodhain, 1976 (1 dog, 2 camels) and Rhipicephalus turanicus Pomerantsev, 1936 (1 camel) is reported. The examined R. cf. camicasi form a sister group to R. sanguineus s.l. tropical lineage at all DNA markers. Dogs were parasitised by Hyalomma dromedarii Koch, 1844 (n = 59), Hyalomma impeltatum Schulze et Schlottke, 1930 (n = 1), Hyalomma excavatum Koch, 1844 (n = 2), Hyalomma turanicum Pomerantsev, 1946 (n = 1) and Hyalomma rufipes Koch,1844 (n = 1). DNA from dog blood (n = 53) from Riyadh confirmed a low prevalence of canine vector-borne pathogens that does not exceed 5.7% for Babesia spp., Mycoplasma spp., Anaplasma platys, Hepatozoon canis and Ehrlichia canis using multiplexed tandem PCR (MT-PCR) and diagnostic PCR. Low prevalence of R. sanguineus s.l. on dogs likely contributed to the low level of canine vector-borne pathogens in Saudi Arabia. We demonstrate that dogs in the central Arabian Peninsula are more commonly parasitised by Hyalomma spp. than R. sanguineus s.l.
Keywords: Animals; Saudi Arabia; Female; Prevalence; Camelus; arachnida jako vektory; ženské pohlaví; velbloudi; nemoci psů; Dog Diseases; Ixodidae; Dogs; prevalence; Male; Saudská Arábie; zvířata; mužské pohlaví; Arachnid Vectors; nemoci přenášené vektory; psi; Vector Borne Diseases; Rhipicephalus sanguineus